2009
DOI: 10.2337/db09-0739
|View full text |Cite
|
Sign up to set email alerts
|

Placental Structure in Type 1 Diabetes

Abstract: OBJECTIVEAlteration of placental structure may influence fetal overgrowth and complications of maternal diabetes. We examined the placenta in a cohort of offspring of mothers with type 1 diabetes (OT1DM) to assess structural changes and determine whether these were related to maternal A1C, fetal hematocrit, fetal hormonal, or metabolic axes.RESEARCH DESIGN AND METHODSPlacental samples were analyzed using stereological techniques to quantify volumes and surface areas of key placental components in 88 OT1DM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 46 publications
3
35
1
1
Order By: Relevance
“…Our data may be consistent with the report stating that diabetic mothers have larger placenta at birth, their offsprings' weight and placental ratio are increased (1,6).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Our data may be consistent with the report stating that diabetic mothers have larger placenta at birth, their offsprings' weight and placental ratio are increased (1,6).…”
supporting
confidence: 93%
“…Placental volumetry is the most common way to characterize placental growth and it is a summary of many dimensions of placental growth. Diabetic state has a profound effect on the microvasculature of developing placenta leading to increased volume of terminal villi and to non-branching angiogenesis in type I diabetes (DM type I) (4)(5) or to degenerative lesions induced by chronic hypoxia in gestational diabetes mellitus (GDM) (6) irrespective of the adequacy of glycemic control (5).…”
Section: Introductionmentioning
confidence: 99%
“…This may be relevant in gestational diabetes [6,86,112,127], a state of greater insulin resistance and hyperinsulinemia than normal pregnancies. In this line, numerous studies have reported that circulating leptin levels, as well as placental leptin and LEPR expression are significantly higher in pregnant women with GDM compared to healthy control women with uncomplicated pregnancy [128,129], providing, at least, a molecular mechanism for the placenta overgrowth previously observed in GDM [99,100]. Others common complications of pregnancy, such as type 1 diabetes mellitus (T1DM) and preeclampsia are also associated with an increase in the concentration of leptin in the maternal blood as well as an increase in placental leptin gene expression [130,131].…”
Section: Role Of Leptin In Pregnancymentioning
confidence: 98%
“…Virtually, all known cytokines are capable of being synthesized and released by cytotrophoblast, syncytiotrophoblast, and resident placental macrophages or Over the last decade, significant advances in our understanding of placental biology have established that placental function is dynamic and influenced by maternal health, and has an important regulatory role in maternal well-being during pregnancy. For example, in women with type 1 diabetes, there is upregulation of placental glycosylation and acylation pathways and a trend toward increased placental weight (Nelson et al 2009, Radaelli et al 2009). Moreover, the progressive development of insulin resistance during pregnancy is due in part to placentally derived cytokines (Rusterholz et al 2007) such as TNF (Kirwan et al 2002) and leptin (Hauguel-de Mouzon & Guerre-Millo 2006).…”
Section: Placental Biologymentioning
confidence: 99%